Clinical and radiological results of posterior ankle endoscopy treatment for the flexor hallusis longus tenosynovitis and os trigonum syndrome - Saylık, Murat (The European Research Journal, 2023)
Objectives: This study investigated the effect of two portal posterior ankle arthroscopy (PAA) procedures using American Orthopaedic Foot and Ankle Society (AOFAS) and Visual Analog Scale (VAS) scores for the treatment of patients with ankle pain associated with Os trigonum (OT) and Flexor hallusis longus (FHL) tenosynovitis. The effect of PAA treatment on the degree and localization of effusion around the FHL tendon was also investigated. Methods: Between March 2016 and August 2021, 41 patients who underwent PAA with the diagnosis of OT and stenosing FHL tenosynovitis, whose arthroscopy video records could be reviewed retrospectively, and who had at least 1 year of follow-up results were included in the study. Patients in the pediatric age group, diabetes patients, patients with inflammatory disease, and those with subtalar and tibiotalar osteoarthritis were excluded from the study. Preoperative and postoperative physical examinations, lateral radiography of the pressing foot, MRI, and the VAS and AOFAS scores were evaluated. In the statistical analysis, data were statistically analyzed using SPSS 19.0 (SPSS, Chicago, Illinois, USA). p < 0.05 was accepted as statistically significant. Results: The mean age was 35.6 years (range: 19-55), among which the mean age of the women was 36.2 years (range: 24-48), and the mean age of the men was 35.2 years (range: 19-55). The mean follow-up was 34 months (range: 14-62). The AOFAS value increased from 38.61 ± 7.176 preoperatively to 89.83 ± 6.34 at the postoperative follow-up, and the difference was statistically significant (p < 0.001). Five patients fully regained their normal function (AOFAS score = 100 points). The VAS value increased from 90 ± 5.916 preoperatively to 18.682 ± 7.688 at the last postoperative follow-up, and the difference was statistically significant (p < 0.001). Pre-PAA FHL tenosynovitis was seen only in zone 1 in 26 patients, zones 1 and 2 in 14 patients, and in zones 1, 2, and 3 in two patients. There was no significant decrease in effusion in the magnetic resonance imaging (MRI) at 1 month after the PAA (p = 0.117). A significant decrease in effusion was observed in the MRI taken at the last control (p < 0.001). Conclusions: In the treatment of patients with ankle pain associated with OT and FHL tenosynovitis, the two-portal PAA treatment was observed to be an effective method that resulted in significant improvement in the AOFAS and VAS scores.